Konsep Manajemen Mutu Pendidikan - N Aslami; M Faisal Alfarisyi (Departement of Mathematics Education, 2023)
Quality is the most important aspect in every educational institution, where quality is believed to be the main capital in facing competition. Therefore, managing an educational institution must be comprehensive and integrated. This is inseparable from how an institution manages that quality. Management of quality management is basically directed to consistently meet consumer needs and achieve continuous improvement in every aspect of educational institution activities. Basically quality management seeks to improve the quality of work, productivity and efficiency through improving both internal and external performance. The quality of education can be seen from the fulfillment of the eight educational standards that must be met by schools. The eight education standards include content standards (implementation and curriculum development), process standards, assessment standards, graduate competency standards, educator and education staff standards, elements management standards in educational institutions, education financing standards, educational facilities and infrastructure standards.